Pengaruh Dukungan Sosial Orang Tua terhadap Pengambilan Keputusan Karier Siswa - Sintawati, Sintawati; Rachmaniar, Ananda; Rayaginansih, Syari Fitrah (Jurnal Dimamu, 2025)
Parental social support is an important factor that affects the career decision-making process of students. This study aims to examine the influence of parental social support on career decision making among 11th-grade students at SMA Negeri Cimanggung in the 2024/2025 academic year. The research uses a quantitative method with simple linear regression analysis to measure the effect of variable X (parental social support) on variable Y (career decision making). Parental social support was measured using a questionnaire developed based on the theory of Sarafino and Smith (2011), while career decision making was measured with an instrument developed based on the theory of Conger (1991). The population of the study consisted of all 427 11th-grade students at SMA Negeri Cimanggung in the 2024/2025 academic year, using a saturated sampling technique. The analysis results showed a regression coefficient of 0.329 with a significance value of 0.000 (p < 0.05). This indicates that there is a positive and significant influence of parental social support on the career decision making of 11th-grade students at SMA Negeri Cimanggung in the 2024/2025 academic year. The contribution of the parental social support variable to career decision making is 14.8%, while the remaining 85.2% is influenced by other factors outside this study.